2000
DOI: 10.1097/00004714-200006000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Zaleplon, Zolpidem, and Triazolam on Memory, Learning, and Psychomotor Performance

Abstract: Twenty-four healthy male and female subjects, who participated in this randomized, double-blind, crossover study, received single nighttime doses of zaleplon 10 mg (therapeutic dose), zaleplon 20 mg, zolpidem 10 mg (therapeutic dose), zolpidem 20 mg, triazolam 0.25 mg (positive control), and placebo. Subjective behavioral ratings and psychomotor tests were completed before and 1.25 and 8.25 hours after administration of the study drug. The Immediate and Delayed Word Recall tests and the Digit Span Test were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 22 publications
4
56
1
Order By: Relevance
“…These effects were seen across measures of attention, memory, and motor coordination. They are consistent with previous studies, where 10 mg of zolpidem at daytime or night-time was found to produce significant impairments of psychomotor performances, attention, and memory from 1-5 h (Berlin et al, 1993;Danjou et al, 1999;Hindmarch et al, 2001) but no residual effects at 8 h or more after administration (Berlin et al, 1993;Fairweather et al, 1992) although delayed memory might be impaired up to 8.25 h after a bedtime administration (Troy et al, 2000). Driving abilities were also impaired 2 h after zolpidem intake, with standard deviations of both speed limit deviation, absolute speed deviation and ideal route deviation, and the number of collisions being significantly affected.…”
Section: Discussionsupporting
confidence: 92%
“…These effects were seen across measures of attention, memory, and motor coordination. They are consistent with previous studies, where 10 mg of zolpidem at daytime or night-time was found to produce significant impairments of psychomotor performances, attention, and memory from 1-5 h (Berlin et al, 1993;Danjou et al, 1999;Hindmarch et al, 2001) but no residual effects at 8 h or more after administration (Berlin et al, 1993;Fairweather et al, 1992) although delayed memory might be impaired up to 8.25 h after a bedtime administration (Troy et al, 2000). Driving abilities were also impaired 2 h after zolpidem intake, with standard deviations of both speed limit deviation, absolute speed deviation and ideal route deviation, and the number of collisions being significantly affected.…”
Section: Discussionsupporting
confidence: 92%
“…The efficacy of these compounds is tied to their exposure, i.e., agents with longer half-lives might be better suited to address sleep maintenance insomnias, but they also tend to have more significant next-day hangover effects that are associated with psychomotor and memory impairments (Drover, 2004). Agents like zaleplon, which have a very short half-life of approximately 1 h, are very useful for sleep-onset insomnia and have no hangover effects, but they are not ideal for sleep maintenance (Troy et al, 2000;Walsh et al, 2000). Inverse agonism of the 5HT 2A receptor seems to produce sleep maintenance without residual psychomotor impairment upon wakening.…”
Section: Discussionmentioning
confidence: 99%
“…In view of its short elimination half-life, one may not have expected residual effects. However, as documented for a number of benzodiazepines (Hindmarch and Ott, 1984) and zolpidem (Roth et al, 1995;Troy et al, 2000;Hindmarch et al, 2001), hypnotic substances with short half-lives are not necessarily free from residual effects. Moreover, as the sleep effects of gaboxadol appear longer-lasting in aged (present study; Lancel et al, 2001) than in young subjects (Faulhaber et al, 1997;Mathias et al, 2001), its elimination half-life probably increases with advancing age.…”
Section: Discussionmentioning
confidence: 99%